(untitled) (GEOAREA | Jurnal Geografi, 2026)
The home industry has grown and developed independently in Mekarlaksana Village. The kicimpring food home industry has expanded employment opportunities and provided business opportunities for the community. The purpose of this study is to analyze the impact of the kicimpring home industry on the welfare of the community in Mekarlaksana Village, Ciparay Subdistrict, Bandung Regency, and to identify the factors that influence the kicimpring home industry. This study aims to determine the impact of the home industry on community welfare and the factors that can influence the home industry. This study uses a descriptive quantitative method with a sample size of 45 people. Data collection methods used in this study include questionnaires, interviews, observations, literature reviews, and documentation. The analysis method used is multiple linear regression analysis. Based on the research results, it can be concluded that home industries have a significant impact on the welfare of the community in Mekarlaksana Village, Ciparay Subdistrict, Bandung Regency. The factors influencing home industries include geographical factors (location, soil, and land), raw materials, employees, marketing, and government policies. The results of this study can serve as a resource for teaching materials in Geography courses at the high school (SMA/MA) level.